Peran Guru Dalam Meningkatkan Kemampuan Membaca Puisi Siswa Kelas III SD Negeri 18 Tanjung Sari - Rahmawati, Lili; Khoiri, Ahmad; Tirsa, Aprima (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2024)
Abstract : : This study aims to determine the teacher's role in improving poetry reading skills at SD Negeri 18 Tanjung Sari. In addition, the purpose of this study was to find out how the teacher improved the poetry reading skills of the students of SD Negeri 18 Tanjung Sari. The study used a descriptive qualitative approach with the research subjects being the third grade guardians of SD Negeri 18 Tanjung Sari and the third grade students of SD Negeri 18 Tanjung Sari, totaling 17 students. Data collection through interview instruments. The data were analyzed by the steps of data collecting, data reduction, data presentation and data clarification. The results of this study indicate that the teacher's role in improving the poetry reading skills of third grade students at SD Negeri 18 Tanjung Sari is as follows: the teacher's task in improving students' poetry reading skills is good, how to improve the poetry reading skills of third grade students at SD Negeri 18 Tanjung Sari is good, the teacher's role in improving the poetry reading skills of third grade students of SD Negeri 18 Tanjung Sari is good. This can be seen from the 10 indicators in this study, the teacher carries out his role to the maximum.Keywords: Teacher's Role, Poetry Reading Ability.Â Abstrak: Penelitian ini bertujuan untuk mengetahui peran guru dalam meningkatkan kemampuan membaca puisi di SD Negeri 18 Tanjung Sari. Selain itu tujuan penelitian ini adalah untuk mengetahui cara guru meningkatkan kemampuan membaca puisi siswa SD Negeri 18 Tanjung Sari. Penelitian menggunakan pendekatan kualitatif deskriptif dengan subyek penelitian adalah wali kelas III SD Negeri 18 Tanjung Sari dan siswa kelas III SD Negeri 18 Tanjung Sari yang berjumlah 17 siswa. Pengumpulan data melalui instrument wawancara. Data dianalisis dengan langkah-langkah data collecting, reduksi data, penyajian data dan klarifikasi data. Hasil penelitian ini menunjukkan bahwa peran guru dalam meningkatkan kemampuan membaca puisi siswa kelas III SD Negeri 18 Tanjung Sari adalah sebagai berikut: tugas guru dalam meningkatkan kemampuan membaca puisi siswa sudah baik, cara meningkatkan kemampuan membaca puisi siswa kelas III SD Negeri 18 Tanjung Sari sudah baik, peran guru dapat meningkatkan kemampuan membaca puisi siswa kelas III SD Negeri 18 Tanjung Sari sudah baik. Hal ini bisa dilihat dari 10 indikator pada penelitian ini, guru melaksaanakan perannya dengan maksimal.Kata Kunci : Peran Guru, Kemampuan Membaca Puisi.